Immunomodulating Activity and Therapeutic Effects of Short Chain Fatty Acids and Tryptophan Post-biotics in Inflammatory Bowel Disease - Russo, Edda; Giudici, Francesco; Fiorindi, Camilla; Ficari, Ferdinando; Scaringi, Stefano; Amedei, Amedeo (Frontiers in Immunology, 2019)
Crohn´s disease (CD) and Ulcerative colitis (UC) are grouped as Inflammatory Bowel Diseases (IBD). The IBD is associated to a multifaceted interplay between immunologic, microbial, genetic and environmental factors. Nowadays, the gut microbiota (GM) dysbiosis has been indicated as a cause in the IBD development, affecting the impaired cross-talk between GM and immune cells. Moreover, recent studies have uncovered a crucial role for bacterial postbiotics (metabolites) in the orchestration of the host immune response, as they could be messengers between the GM and the immune system. In addition, transgenic mouse models showed that SCFAs (Short Chain Fatty Acids) and Tryptophan (Trp) postbiotics play important immunomodulatory effects, regulating both innate and adaptive immune cell generation, their function and trafficking. Here, we present an overview on the main microbial postbiotics and their effects on the gut mucosa with specific emphasis on their relevance for IBD. Finally, we discuss the therapeutic potential of SCFA and Trp postbiotics on IBD through approaches based on the “immunonutrition”.